JURNAL KELLY LAURA BAD_EVALUASI KEPUASAN PASIEN TERHADAP PELAYANAN KEFARMASIAN DI INSTALASI FARMASI RAWAT JALAN UPTD PUSKESMAS SUNGAI BOH - Kelly Laura Bad (Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2022)
Patient satisfaction is one indicator of service quality in pharmaceutical services. Evaluation of patient satisfaction is one way to find out the services provided have been carried out properly. This study aims to determine the characteristics and level of patient satisfaction in Pharmaceutical Services. The type of research used is descriptive research with a cross sectional design and distribution of questionnaires to patients who receive pharmaceutical services at the Outpatient Pharmacy Installation of UPTD Sungai Boh. This research was conducted at the Pharmaceutical Services section at the Outpatient Pharmacy from June to July 2022 with a total of 100 respondents. The analysis technique uses the SERVQUAL method to determine the respondent's value and the data will be analyzed using a Likert scale, then the results are displayed in the form of a percentage table. Based on the results of the study, data on respondents' satisfaction with pharmaceutical services at the Outpatient Pharmacy Installation of Sungai Boh Health Center showed that 30% were very satisfied with pharmaceutical services, 54% were satisfied with pharmaceutical services, and 16% of respondents said they were quite satisfied. Keywords: Satisfaction Evaluation; Public Health Center; SERVQUAL.